Beyond the rhetoric promises of the Egyptian sexual harassment law: a study of the relationship between law and domination - Abdel Akher, Nihal Mostafa (AUC Knowledge Fountain, 2014)
After decades of male supremacy, it is not surprising to find that social institutions, including the government and the legal system, have a role in maintaining and reproducing the established order of domination. This study seeks to understand the relationship of law to domination. It argues that law serves the dominant society in two ways. The first is that law legitimates power of the established order, relations of domination, and itself. This happens when the practice of law reinforces the established order of domination while maintaining its own principle of fairness. This means that law proclaims a deceitful image of law for all, while in actuality it sustains the unequal distribution of social power. The society, including both powerful and powerless classes, accepts the neutrality and objectivity of law and through this, law legitimates itself and maintains the structure. The second is that law contributes to the reproduction of the established order of domination. In this approach, law is a set of rules, developed throughout history, which assign to each member his/her position in society, whether it is dominant or submissive. This law is not an external force. Rather it is an internal force that employs certain social groups to reinforce the prevailing social norms. The influence of such law educates men into masters of society and women into slaves of the masters. This happens when law reflects the male dominant point of view in its content. Based on these arguments, this study uses the Egyptian sexual harassment law as an example of how law maintains and reproduces the established order of domination. It argues that Egyptian law serves men, first, by legitimating power of the social structure that subordinates women to men and second, by constructing subjects and turning them into dominant male and submissive female in accordance with their social status.